Diversity, dynamics and effects of long terminal repeat retrotransposons in the model grass Brachypodium distachyon - Stritt, Christoph (John Wiley and Sons Inc., 2019)

(untitled) (New Phytol)
Transposable elements (TEs) are the main reason for the high plasticity of plant genomes, where they occur as communities of diverse evolutionary lineages. Because research has typically focused on single abundant families or summarized TEs at a coarse taxonomic level, our knowledge about how these lineages differ in their effects on genome evolution is still rudimentary. Here we investigate the community composition and dynamics of 32 long terminal repeat retrotransposon (LTR‐RT) families in the 272‐Mb genome of the Mediterranean grass Brachypodium distachyon. We find that much of the recent transpositional activity in the B. distachyon genome is due to centromeric Gypsy families and Copia elements belonging to the Angela lineage. With a half‐life as low as 66 kyr, the latter are the most dynamic part of the genome and an important source of within‐species polymorphisms. Second, GC‐rich Gypsy elements of the Retand lineage are the most abundant TEs in the genome. Their presence explains > 20% of the genome‐wide variation in GC content and is associated with higher methylation levels. Our study shows how individual TE lineages change the genetic and epigenetic constitution of the host beyond simple changes in genome size.